Physical and Mechanical Properties of Engineered Coconut Trunk Veneer (ECTV) for Interior Products - Yanti, A. K.; Said, A.; Hamid, A. S.; Hamdan, H.; Kamal, Izran; Khairul, M.; Razali, A. K.; Azrena, A. K. (International Coconut Community, 2013)
A study was undertaken to investigate the physical and mechanical properties of engineered coconut (Cocos nucifera) veneer (ECTV). The coconut trunks (40 – 50 years old) were obtained from Hutan Melintang, Perak and were peeled into veneers at Bestgrade Sdn. Bhd. The veneers were obtained from two different parts of coconut trunks viz inner and outer which were used to fabricate 5-ply engineered coconut veneers. The ECTVs were fabricated at FRIM’s Bio-Composite Laboratory. They were manufactured with urea formaldehyde (UF) resin and with three combinations namely 100% inner, 100% outer and alternate outer & inner veneers (mix). The densities for the engineered veneers made of 100% outer, 100% inner, and mixed layers were 944.1 kg/m3, 858.15 kg/m3 and 891.11 kg/m3, respectively. Results showed that the Modulus of Rupture (MOR) of the ECTV made from 100% outer veneers had the highest mean MOR value (88.69 MPa), followed by those made from the mixed veneers (74.35 MPa) and 100% inner (58.44 MPa), respectively. On the other hand, the Modulus Of Elasticity (MOE) values were 10.12 Mpa for outer, 8,210 Mpa for inner and 10,075 Mpa for mixed. Overall, the testing results showed that the ECTV met the standard requirements.